Responses of Broiler Chicks to Non-Phytate Phosphorous Levels and Phytase Supplementation - Karimi, Ahmad (International Journal of Poultry Science, 2006)
Supplementation of broiler diets with phytase has proven to be an effective and realistic method for enhancing the digestibility of phytic acid in monogastric animals. This study was conducted to evaluate the effect of microbial phytase (RonozymeP) supplementation in broiler chicks fed different levels of non-phytate phosphorus (nPP) on performance. Five hundred and seventy six day old mixed sex, Ross broiler chicks were distributed randomly into 6 dietary treatments (three replicate /each 32 chicks). Data were analyzed as a 3×2 factorial arrangement with three levels of nPP (0.45, 0.38, and 0.31 % during starter and 0.43, 0.36, and 0.29 % during grower and finisher periods) and two levels of phytase (0 and 500 F.T.U/kg) in each period. The results showed that chicks fed with lower nPP diets had significantly lower body weight at 40 and 50d; lower daily gain during 20-40d and 0-50 d; and higher feed conversion ratio during 20-40d period. Phytase supplementation to the diets had only significantly increased feed intake during 21-40d period. The interactions between nPP levels and phytase supplementation on body weight at 40d and FCR during 0-20d was significant, in which the BW of the chicks fed lowest nPP diets was improved by phytase, whilst those of chicks fed high nPP diets was adversely affected by phytase supplementation.